Strengthening islamic cultural heritage of the Malays in Malaysia in the post global society - Farok Zakaria (2011)
Malay and Islamic religion has exist long ago in the Malaysian soil, bringing about the Malay Islamic arts and culture. The Malay Islamic Arts and Culture has been the epitome of a Malays in Malaysia. Recently, the wave of globalization has transformed some Malay Islamic Arts and Culture to be less significance in the daily life of a Malay Moslem. The role of Malay Islamic Arts and culture is slowly becoming alien to the heart of Malay Moslems. Many factors has contributed to the phenomenon of less popularity in the Malay Islamic Arts and Culture. The Malays themselves have succumbed to many western influences brought by the introduction of technologies and education. Adopting and practicing modern living with many constraints such as time, monetary and space has led many Malay Moslem to slowly forget their precious gem- The Malay Islamic Arts and Culture. This paper highlights the variety of Malay Islamic arts and culture practice as rituals by Malays in Malaysia. It will also discussed the factors contributing to the dying of these arts and culture as well as recommending some suggestions in curbing the ever disturbing scenarios of Malay Islamic Arts and Culture.